Funktionsdiagnostische Möglichkeiten bei fortgeschrittenem oder präterminalem Glaukom - Scheuerle, Alexander F.; Schiefer, Ulrich; Rohrschneider, Klaus (Der Ophthalmologe, 2012)
The visual functional diagnostics for patients with advanced glaucomatous optic neuropathy are subject to challenge. Reduced visual acuity, instable fixation and extensive scotomata frequently lead to incorrect results within the central 30° or 24° field. Static automatic perimetry (SAP) in particular is often hampered by extended examination time and fatigue especially in older patients. Focusing of the examination towards the central 10° field using a dense test grid (2° distance between stimulus locations) allows a more exact assessment of the small remaining central island. Tailoring the examination area towards the central 10° field may be useful even in cases with a mean deviation (MD) of 15 dB. In cases of advanced visual field loss kinetic perimetry is superior to static perimetry for various reasons: sharply demarcated visual field defects can be comparatively easily delineated (edge detection); the results are more reliable because fixation can be easily controlled and fatigue is much less pronounced in this interactive examination procedure. However, manual kinetic visual field testing within the central 5° using the conventional Goldmann perimeter is almost impossible due to technical reasons. Semi-automated kinetic perimetry, presenting moving stimuli along interactively defined vectors is a useful tool under these circumstances. The standardized presentation of kinetic stimuli is also feasible within the pericentral region and has particular advantages also with regard to follow-up examinations. On the other hand, detection and delineation of small visual field remnants are comparatively difficult to handle with this kind of vector-based kinetic perimetry.